1978
DOI: 10.1111/j.1745-9125.1978.tb01398.x
|View full text |Cite
|
Sign up to set email alerts
|

The Index of Southernness Revisited

Abstract: A study by Gastil concludes that the Southern area of the United States constitutes a regional subculture of violence. Loftin and Hill (1974) empirically challenge Gastil's findings at the ecological level of analysis. This study adds a further dimension to that line of research by examining violence‐related items from a national survey at the individual level of analysis. Results fail to confirm the existence of a divergent value system among Southerners today. It is suggested that if a “regional culture of v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1985
1985
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(7 citation statements)
references
References 4 publications
(8 reference statements)
0
7
0
Order By: Relevance
“…In addition, early researchers suggested that notions of chivalry and vengeance for breaches of trust, injuries to family, or threats to women are consistent with the feudal spirit of the Old South that was economically and politically dominated by whites (see Ellison 1991 for a review). More importantly, the findings from several studies support this notion: white males from the South are more likely to approve of assaultive behavior or violence compared to blacks (Dixon and Lizotte 1987;Doerner 1978;Ellison 1991).…”
mentioning
confidence: 90%
“…In addition, early researchers suggested that notions of chivalry and vengeance for breaches of trust, injuries to family, or threats to women are consistent with the feudal spirit of the Old South that was economically and politically dominated by whites (see Ellison 1991 for a review). More importantly, the findings from several studies support this notion: white males from the South are more likely to approve of assaultive behavior or violence compared to blacks (Dixon and Lizotte 1987;Doerner 1978;Ellison 1991).…”
mentioning
confidence: 90%
“…Since the Loftin and Hill (1974) study, a number of other researchers have also found little support for the cultural thesis (cf. Erlanger, 1976;Doerner, 1978;O'Connor and Lizotte, 1978). Thus, there is also much support for the alternative explanation.…”
Section: Thementioning
confidence: 71%
“…Although there are clearly similar issues pertaining to both approaches to understanding cultural sources of violence, it is also true that different methodological approaches are necessary to successfully study them. Although the culture as values approach has been most frequently studied using closed ended survey instruments in general population surveys (Ball-Rokeach, 1973;Borg, 1997;Cao, Adams, & Jensen, 1997;Doerner, 1978;Ellison, 1991;Erlanger, 1975;Hayes & Lee, 2005), the culture as strategies for action approach requires sensitivity to a host of additional issues. Specifically, to analyze when violence is a viable strategy of action, the methodological logic of variable-based quantitative analysis is less appropriate.…”
Section: Methodsmentioning
confidence: 99%
“…General population surveys are the main method used to examine this issue. Based on survey data, Doerner (1978) reports that southerners are no more likely to approve of punching an adult male stranger than respondents from other regions, while Hayes and Lee (2005) report that southern White males from rural areas are more likely to support assaultive violence in situations where general approval is very low to begin with. Erlanger (1975) finds that southern Whites and Blacks are no more likely to approve of various forms of assaultive violence than nonsouthern Whites and Blacks, while Cao, Adams, and Jensen (1997) report that Whites are more supportive of "defensive violence," whereas southerners are more supportive of "offensive violence."…”
Section: Background and Conceptual Framework Values Modelsmentioning
confidence: 99%